Decolonization in a higher education STEMM institution - is 'epistemic fragility' a barrier? (UCL Press, 2021)
Central to the decolonial debate is how high-income countries (HICs) have systematically negated ways of knowing from low- and middle-income countries (LMICs), and yet the paucity of empirical decolonization studies leaves educators relatively unsupported as to whether, and how, to address privilege in higher education. Particularly in science, technology, engineering, mathematics and medicine (STEMM) institutions, there are few published examples of attempts to engage faculty in these debates. In 2018-19, we invited faculty on a master's in public health course to engage with the decolonization debate by providing: (1) descriptive reading list analyses to all 16 module leads in the master's programme to invite discussion about the geographic representation of readings; (2) an implicit association test adapted to examine bias towards or against research from LMICs; (3) faculty workshops exploring geographic bias in the curriculum; and (4) interviews to discuss decolonization of curricula and current debates. These initiatives stimulated debate and reflection around the source of readings for the master's course, a programme with a strong STEMM focus, and the possibility of systemic barriers to the inclusion of literature from universities in LMICs. We propose the notion of epistemic fragility, invoking DiAngelo's (2011) 'white fragility', because some of the responses appeared to result from the challenge to perceived meritocracy, centrality, authority, individuality and objectivity of the HIC episteme that this initiative invites. We posit that the effortful reinstatement of a status quo regarding knowledge hierarchies in the global context, although not a representative reaction, can lead to a significant impact on the initiative in general. Efforts to decolonize curricula require actions at both the individual and organizational levels and, in particular, a managed process of careful engagement so that fragility reactions, if and where they occur, are given the time and space to be navigated in the open. Based on our experiences, we offer recommendations for policy and practice for those engaged in this movement and potential research questions to explore epistemic fragility in higher education.